Parâmetros da água alteram a excreção de resíduos nitrogenados e de fósforo e o comportamento de juvenis de jundiá (Rhamdia quelen) - Golombieski, Jaqueline Ineu (2013)
In the first study examined ammonia, urea, creatinine, protein, nitrite, nitrate, and phosphorus (P) excretion at different water hardness, humic acid or pH levels in silver catfish (Rhamdia quelen) juveniles. The fish were exposed to different levels of water hardness (4, 24, 50, or 100 mg CaCO3 L-1), humic acid (0, 2.5 or 5.0 mg L-1) or pH (5.0, 6.0, 7.0, 8.0, or 9.0) for 10 days. The overall measured nitrogen excretions were 88.1% (244 423 μmol kg-1 h-1) for ammonia, 10.9% (30 52 μmol kg-1 h-1) for creatinine, 0.02% (0.05 0.08 μmol kg-1 h-1) for protein, 0.001% (0.002 0.004 μmol kg-1 h-1) for urea, 0.5% (0.64 3.6 μmol kg-1 h-1) for nitrite, and 0.5% (0.0 6.9 μmol kg-1 h-1) for nitrate, and these proportions were not affected by water hardness or humic acid levels. The overall P excretion in R. quelen was 0.14 2.97 μmol kg-1 h-1. Ammonia excretion in R. quelen usually was significantly higher in the first 12 h after feeding, and no clear effect of water hardness, humic acid levels and pH on this daily pattern of ammonia excretion could be observed. Water hardness only affected the ammonia and P excretion of R. quelen juveniles in the initial and fifth days after transfer, respectively. The exposure of this species to humic acid decreased ammonia excretion after 10 days of exposure but did not affect P excretion. An increase in pH decreased ammonia and increased creatinine excretion but did not change P excretion in R. quelen. Therefore, when there is any change on humic acid levels or pH in the culture of this species nitrogenous compounds must be monitored because their excretion rates are variable. On the other hand, P excretion rates determined in the present study are applicable to a wide range of fish culture conditions. The aim of the second study was to determine the preferred pH in silver catfish Rhamdia quelen acclimated to different water hardness and the effect of shelters and infection by Ichthyophthirius multifiliis. Fish were acclimated for two weeks at different water hardness levels (4, 24, 50, or 100 mg CaCO3 L-1) and then transferred to a polyethylene tube with a pH gradient ranging from 3.5 to 11.7. The position of the fish in the pH gradient was observed at 1, 2, 4, 6, 8, 10, and 12 h after transference. Acclimation to different water hardness did not change pH preference of uninfected silver catfish (pH 7.30-7.83), and the presence of a shelter at the preferred pH or outside this preferred pH did not change the chosen pH range, either. Consequently silver catfish favored the acid-base regulation over shelter seeking tendency. Juveniles infected with I. multifiliis acclimated to water hardness of 24 mg CaCO3 L-1 preferred alkaline pH (9.08-9.79). This choice is not explained by the higher Na+ levels at alkaline pH compared to neutral pH because infected and uninfected fish choose the same waterborne Na+ levels in a Na+ gradient with the same pH.